Analysis of low carbon super credit policy efficiency in European Union greenhouse gas emissions. (15th March 2015) - Álvarez, Roberto; Zubelzu, Sergio; Díaz, Guzmán; López, Alberto
Abstract: In this paper we address the current European Union's support policy for BEV (battery electric vehicles) manufacturing under the Super-credit modality, and its actual relationship with the reduction of carbon emissions derived from the use of battery electric vehicles (BEV). Particularly, we have estimated the BEV associated carbon emissions through the method provided by Intergovernmental Panel on Climate Change (IPCC). In this sense, we have employed a BEV model to investigate the BEV emissions by country in the EU according to the regional electricity mix. We additionally have accounted for the particularities of real-world driving, which further affects the results. We have employed a measure of driving aggressiveness by modifying the standard benchmarking driving cycle fostered by the European Union and of necessary application by vehicle manufacturers—the NEDC—to show that BEV emissions are not negligible when compared with internal combustion vehicles; mainly in urban environments. On the whole, in this paper we provide a revision framework of the Super Credits meant to support the increase of the BEV fleet in the European Union. In its current form, the Super-credits support policy is a constant ratio depending on the manufactured internal combustion vehicles. We claim, however, that they should depend on the BEV recipient country instead. By revising the European electricity mix, we demonstrate for instance that countries such as Poland, though indirectly, largely exceed the allowed limits of CO2 emissions derived from the upstream generation of electricity required to load the BEV. Highlights: Super-credit support policy is aimed at promoting the manufacturing of BEV in the EU. It does not account for upstream electricity generation in the BEV user country. We analyze the generation emissions ensuing from the use of the BEV in EU countries. We show that indirect carbon emissions in some countries exceed proposed targets. The quantity-based support policy should account for the BEV destination country.